2003
DOI: 10.1046/j.1440-1681.2003.03863.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute and chronic effects of dinner with alcoholic beverages on nitric oxide metabolites in healthy men

Abstract: 1. The present study investigated the acute and chronic effect of dinner with alcoholic beverages on serum nitric oxide (NO) metabolites, namely nitrate and nitrite (NOx), in 11 healthy, non-smoking middle-aged men. 2. In a randomized, diet-controlled, cross-over trial, subjects consumed dinner with four glasses of red wine, beer, spirits (Dutch gin) or sparkling mineral water (control) for 3 weeks. At the end of each 3 week period, serum NOx concentrations were measured just before and 1, 5 and 13 h after din… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Food intake acutely and transiently increased serum NOx concentrations, an effect that was slightly attenuated if combined with alcoholic beverages. Chronic moderate alcohol consumption had no effect on the serum NOx concentration 37) .…”
Section: Discussionmentioning
confidence: 79%
“…Food intake acutely and transiently increased serum NOx concentrations, an effect that was slightly attenuated if combined with alcoholic beverages. Chronic moderate alcohol consumption had no effect on the serum NOx concentration 37) .…”
Section: Discussionmentioning
confidence: 79%
“…The beverage, which was made from vinegar and garlic, can be used to promote the same mechanism for reduction of NO metabolites. One study showed that after food consumption at dinner, the intake of beverages, especially alcoholic beverages, caused an increase of NO, but regular use reduces this effect (Sierksma, Van Der Gaag, Grobbee, & Hendriks, 2003). Gingerols and shogaols are bitter phenolic composites which are present in ginger and have antiinflammatory effects (Venkatesha, Berman, & Moudgil, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…FMD depends on production of NO and other vasodilators by the endothelium, and inflammation have the potential to impair FMD by reducing the bioavailability of NO (29). An 11% decrease in serum concentration of NO metabolites (nitrate and nitrite) has been demonstrated when measured in healthy men 1 h after dinner taken with alcoholic beverages (30). As NO levels are influenced by nitrate-rich foods and alcoholic beverages, they were measured when they had reached a steady-state plasma concentration (after at least 14 h of fasting).…”
Section: Discussionmentioning
confidence: 99%